2021
DOI: 10.1097/01.nurse.0000743284.73649.7a
|View full text |Cite
|
Sign up to set email alerts
|

Does alarm fatigue start in nursing school?

Abstract: indicated a general decrease in sensitivity over an 18-month period. Nursing students with previous healthcare experience also noted decreased sensitivity to bathroom call bells and fall and safety alarms. Conclusion: Alarm fatigue was recognized among the surveyed nursing students. Nurse educators also identified a performance-based strategy to increase student awareness of alarm fatigue and evidencebased strategies to minimize desensitization to alarms in both education and practice. CLINICAL ALARMS are cruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…As a control, the "relax" tempo setting was utilized for all participants. Statistical terminology [13][14][15][16] Paired t-test: compares two sets of observations to evaluate the differences. P-value: evaluates the strength of the hypothesis; smaller P-values (≤.05) suggest lower probability that the statistical outcomes are attributable to chance alone, suggesting that the intervention is the source of the identified change.…”
Section: Resultsmentioning
confidence: 99%
“…As a control, the "relax" tempo setting was utilized for all participants. Statistical terminology [13][14][15][16] Paired t-test: compares two sets of observations to evaluate the differences. P-value: evaluates the strength of the hypothesis; smaller P-values (≤.05) suggest lower probability that the statistical outcomes are attributable to chance alone, suggesting that the intervention is the source of the identified change.…”
Section: Resultsmentioning
confidence: 99%
“…A survey conducted in the United States reported that even nursing students experienced alarm fatigue during the 18 month study period. 37 Medical devices were necessary and useful for patient safety in clinical practice, but the workload related to false alarms was heavy. 7,38,39 According to the previous studies, the rate of false alarms from different patient monitors ranged from 52.3% to 86%.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al note that nurses working in the ICU for no more than 10 years had less knowledge of alarm fatigue than those with more seniority [31]. There are also reports that show that raising awareness of Alarm Fatigue should start as early as during nursing education [32].…”
Section: Discussionmentioning
confidence: 99%